2018
DOI: 10.1029/2018jd028875
|View full text |Cite
|
Sign up to set email alerts
|

Simple Parameterization of Aerodynamic Roughness Lengths and the Turbulent Heat Fluxes at the Top of Midlatitude August‐One Glacier, Qilian Mountains, China

Abstract: The fluxes of sensible heat (H) and latent heat (LE), which are generally the important parts of the energy and mass balances over glacier surfaces, are widely quantified by the bulk method. However, due to the difficulty of determining the aerodynamic roughness length z 0m in this method, H and LE values may still have large uncertainties with significant inaccuracy. To acquire reliable varying and intrinsic z 0m values, new simpler parameterizations for z 0m values at different ranges of the friction velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Ice surface z 0 was generally larger than snow surface and smaller than patch snow-covered surface. Our results match values reported in studies reporting results ranging from 0.1 to 6.9 mm in Qilian mountain glaciers (Guo et al, 2018;Sun et al, 2018). Our results showed that z 0 reached its maximum at the end of the summer melt, which matched wind profile measurements by Smeets and Broeke (2008).…”
Section: Spatial and Temporal Variability Of Zsupporting
confidence: 92%
See 3 more Smart Citations
“…Ice surface z 0 was generally larger than snow surface and smaller than patch snow-covered surface. Our results match values reported in studies reporting results ranging from 0.1 to 6.9 mm in Qilian mountain glaciers (Guo et al, 2018;Sun et al, 2018). Our results showed that z 0 reached its maximum at the end of the summer melt, which matched wind profile measurements by Smeets and Broeke (2008).…”
Section: Spatial and Temporal Variability Of Zsupporting
confidence: 92%
“…Micro-topography, wind profile and eddy covariance methods generate a wide range of z 0 values for snow and ice surfaces (Grainger and Lister, 1966;Munro, 1989;Bintanja and Broeke, 1995;Schneider, 1999;Hock and Holmgren, 2005;Brock et al, 2006;Andreas et al, 2010;Gromke et al, 2011). In this study, z 0_profile , z 0_DEM and z 0_DEM showed similar variation pattern during the melting season.…”
Section: Spatial and Temporal Variability Of Zsupporting
confidence: 63%
See 2 more Smart Citations
“…The average RMSE of CFDAP decreased about 66.48 and 83.07 mm than that of FDAP and original TRMM data from 2006 to 2015. Additionally, the distribution of precipitation also changed, with the main trend still showing a gradual increase from southwest to northeast, but exhibiting a notable increase in precipitation in the high-elevation area, where the total amount of precipitation is roughly the same as some observed points in Laohugou No.12 Glacier [41], August-one Glacier [42]. To verify the effectiveness of the improved method, we used the original NDVI instead of PNDVI in the statistical model (4), and the parameters were obtained with statistical relationships.…”
Section: Downscaled Annual Precipitation and Validationmentioning
confidence: 88%